Structural characterization and antioxidant activity of pectic polysaccharides from Veronica peregrina L. - Yan, Su; Liu, Xianbin; Wang, Yuwen; Yang, Xiaomin; Bai, Lu; Sun, Lin; Zhou, Yifa; Cui, Sisi (Frontiers in Nutrition, 2023)
Pectins are a class of acidic polysaccharides with complex structures. Different pectin molecules are composed of different domains, which have an important impact on their biological activity. In this study, two pectic polysaccharides (WVPP-A2b and WVPP-A3b) with molecular weights of 48.7 × 10 4 and 77.6 × 10 4 kDa, respectively, were isolated from Veronica peregrina L. Structural analysis showed that both contained homogalacturonan (HG), rhamnogalacturonan I (RG-I), and rhamnogalacturonan II (RG-II) domains with a mass ratio of 2.08:2.64:1.00 and 3.87:4.65:1:00, respectively. The RG-I domain contained an arabinogalactan II backbone and arabinans consisting of t-Araf, (1→5)-α-Araf, and (1→3,5)-α-Araf. WVPP-A3b also contained short chains consisting of the [t-α-Araf-(1→5)-α-Araf-(1→] structural unit. WVPP-A3b showed stronger ability to scavenge DPPH, hydroxyl, and ABTS radicals, which was potentially associated with its high content of galacturonic acid and presence of the HG domain. The results provide information for enhancing knowledge of the structure-activity relationship of pectic polysaccharides from V. peregrina and their potential application in the healthcare food field.